Novel immunohistochemical marker in the differential diagnosis of sex cord-stromal tumors: SF-1 (Annals of Medical Research, 2022)
Aim: Sex cord-stromal tumors are relatively uncommon tumors which constitute approximately 8% of all primary ovarian neoplasms. Morphologic differentiation of non-SCST from SCSTs can be challenging due to microscopic overlap. Immunohistochemistry is beneficial in challenging cases. Inhibin and calretinin have limited sensitivity and specificity, a more sensitive marker is required. SF-1 is known as a promising immunohistochemical marker in the differentiation of SCST from non-SCST ovarian tumors. For this purpose, various non-SCSTs (metastatic and non-metastatic) having morphologic overlap with SCSTs, and multiple SCSTs were stained with SF-1 antibody to elucidate its importance in morphologically challenging cases.Materials and Methods: Twenty-three SCST, 40 non-SCSTs, and an ectopic adrenal tissue were stained with SF-1, and also the percentage and the intensity were scored. SF-1 immunoreactivity was seen in all 23 SCST with varying degrees of intensity and percentage. In contrast, non-SCSTs were negative in all regarding to SF-1. Ectopic adrenal gland tissue and ovarian stroma are positive as non-tumoral lesions.Results: In our series, SF-1 immunoreactivity was seen in all 23 SCST and ectopic adrenal tissue with varying degrees of intensity and diffuseness. In contrast, non-SCSTs were all negative concerning SF-1. In addition; we observed nuclear positivity with SF-1 in 15-75% of the sclerosing stromal tumor cells, whereas inhibin and calretinin were negative in all 4 cases.Conclusion: Our data shows that SF-1 is a nuclear, reliable and surrogate marker for all SCSTs, and can be used routinely.
Keywords: Immunohistochemistry; differential diagnosis; NR5A1/SF-1; sex cord-stromal tumors